Topical TWEAK Accelerates Healing of Experimental Burn Wounds in Mice - Liu, Jing; Peng, Lingling; Liu, Yale; Wu, Kunyi; Wang, Sijia; Wang, Xuening; Liu, Qilu; Xia, Yumin; Zeng, Weihui (Frontiers in Pharmacology, 2018)
The interaction of tumor necrosis factor-like weak inducer of apoptosis (TWEAK) and its receptor fibroblast growth factor inducible 14 (Fn14) participates in inflammatory responses, fibrosis, and tissue remodeling, which are central in the repair processes of wounds. Fn14 is expressed in main skin cells including dermal fibroblasts. This study was designed to explore the therapeutic effect of TWEAK on experimental burn wounds and the relevant mechanism underlying such function. Third-degree burns were introduced in two BALB/c mouse strains. Recombinant TWEAK was administrated topically, followed by the evaluation of wound areas and histologic changes. Accordingly, the downstream cytokines, inflammatory cell infiltration, and extracellular matrix synthesis were examined in lesional tissue. Moreover, the differentiation markers were analyzed in cultured human dermal fibroblasts upon TWEAK stimulation. The results showed that topical TWEAK accelerated the healing of burn wounds in wild-type mice but not in Fn14-deficient mice. TWEAK strengthened inflammatory cell infiltration, and exaggerated the production of growth factor and extracellular matrix components in wound areas of wild-type mice. Moreover, TWEAK/Fn14 activation elevated the expression of myofibroblastic differentiation markers, including alpha-smooth muscle actin and palladin, in cultured dermal fibroblasts. Therefore, topical TWEAK exhibits therapeutic effect on experimental burn wounds through favoring regional inflammation, cytokine production, and extracellular matrix synthesis. TWEAK/Fn14 activation induces the myofibroblastic differentiation of dermal fibroblasts, partially contributing to the healing of burn wounds.